Uniting the Sun’s Hale magnetic cycle and “extended solar cycle” paradigms - McIntosh, Scott W.; Scherrer, Philip H.; Svalgaard, Leif; Leamon, Robert J. (Frontiers in Astronomy and Space Sciences, 2022)
Through meticulous daily observation of the Sun's large-scale magnetic field the Wilcox Solar Observatory (WSO) has catalogued two magnetic (Hale) cycles of solar activity. Those two (~22-year long) Hale cycles have yielded four (~11-year long) sunspot cycles (numbers 21 through 24). Recent research has highlighted the persistence of the ``Extended Solar Cycle'' (ESC) and its connection to the fundamental Hale Cycle - albeit through a host of proxies resulting from image analysis of the solar photosphere, chromosphere and corona. This short manuscript presents the correspondence of the ESC, the surface toroidal magnetic field evolution, and the evolution of the Hale Cycle. As Sunspot Cycle 25 begins, interest in observationally mapping the Hale and Extended cycles could not be higher given potential predictive capability that synoptic scale observations can provide.